NEW COMBINATION SUPPOSITORIES OF LORNOXICAM AND ALOIN FOR RHEUMATOID ARTHRITIS - Saeed, Ashti M H; Alaayedi, Maryam H; Alshohani, Athmar Dh H (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â  Â Objective: The objective of our current work is to formulate, optimize and evaluate new combination rectal suppositories as a treatment for rheumatoid arthritis that contains both lornoxicam and aloin. Both are strong anti-inflammatory agents, and a combination of both may have synergistic effect as an anti-inflammatory treatment. Methods: Rectal suppositories containing 8 mg lornoxicam and 200 mg aloin were formulated by heat fusion method. Different combinations of different molecular weights of polyethylene glycol (PEG) were used for the formulated suppositories. The formulated suppositories were evaluated for their visual appearance, weight variation, hardness, friability, disintegration time, melting temperature, and drug content uniformity. Results: All the formulations prepared were within the required limits for USP. When the release study was performed, both drugs were released from all the formulations prepared. However, formulation F7 which is composed of PEG 400 30.88% (w/w): PEG 4000 46.32% (w/w) was superior to other formulations in which more than 80% of both drugs loaded were released after 35 min. The presence of both drugs in the same suppository did not affect their release. Conclusion: A new combination suppositories have been obtained where the two combined drugs were released fast without interference with each other release. The proposed new combination has the potential to be used as a strong analgesic and anti-inflammatory treatment compared to using lornoxicam or aloin alone.